Directory of graduate research 1993 : faculties, publications, and doctoral and master's theses in departments or divisions of chemistry, chemical engineering, biochemistry, medicinal/pharmaceutical chemistry, clinical chemistry and polymer science at universities in the United States and Canada / prepared by the Committee on Professional Training. (1993)
Summary goes here